2014
DOI: 10.1007/s00595-014-0971-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between endovascular repair and open surgery for isolated iliac artery aneurysms

Abstract: The management of isolated IAAs with both endovascular and open repair can be accomplished with very low morbidity rates. Therefore, endovascular repair can be considered an alternative treatment for isolated IAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Compared with surgery, the endovascular approach not only provides minimal invasiveness but also offers long-term efficacy. 1,2,7,11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with surgery, the endovascular approach not only provides minimal invasiveness but also offers long-term efficacy. 1,2,7,11…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, this study has found that endovascular treatment of isolated IAAs is a safe and effective minimally invasive alternative to traditional open surgery (Table 4). 6,7,11,20…”
Section: Discussionmentioning
confidence: 99%
“…The decision to proceed with open or endovascular was surgeon dependent and affected by the patient’s anatomy and comorbidities. Due to the nature of observational study, the preoperative characteristics of patients were different in some included studies 14,15,17 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that aneurysms located deep in the pelvic cavity are very difficult to treat surgically, and the operations to do so have high mortality rates . In the other hand, it has reported that isolated iliac artery aneurysm can be can be safely and effectively treated by open repair or endovascular repair . Moreover, if rupture has occurred, the urgency of the patient's condition, their hemodynamics, and the presence of retroperitoneal hematoma can further complicate the open procedure.…”
Section: Discussionmentioning
confidence: 99%